Evaluation of the reuse of organic solid waste generated by catering services - Castillo Zavaleta, Carlos Orlando (2023)
The purpose of this article is to compare alternatives for the reuse of organic solid waste generated by catering services, this research will be carried out by verifying studies no older than 5 years to date, denoting their progress in each method. to be used, by comparing the methods and results of each study, in order to define the best reuse alternative, taking into account the cost benefit, the advantages, disadvantages and the feasibility of each study. Therefore, in the present investigation, the result was to opt for the reuse of composting, because it is a process that generates great profits at little cost, in general 80% of organic waste is reused, on the other hand, we have the use through the generation of energy by obtaining biogas, being a slightly more complicated process due to the higher incidence in cost/benefit of this reuse alternative. Therefore, the article concludes that these 2 reuse processes are effective, of course one is cheaper and simpler than the other, but noting that both generate economic benefits.